GENETIC DIVERGENCE STUDIES FOR MORPHO-PHYSIOLOGICAL CHARACTERS INCLUDING SEED YIELD IN CHICKPEA (Cicer arietinum L.) - K. BHANU REKHA (The Journal of Research ANGRAU, 2016)
Utilization of genetically variable accessions in plant breeding programmes helps in developing potential breeding material for the future. The present investigation was carried out with thirty genotypes of chickpea to study the nature and magnitude of genetic divergence using Mahalanobis’s D2 Statistics. The data was recorded on eleven important yield and yield attributing traits from the genotypes raised in Randomized Block Design with three replications.Based on genetic diversity values thirty chickpea genotypes were grouped into five clusters. The maximum inter cluster distance was observed between cluster III and V followed by cluster I and V, cluster III and IV, cluster I and IV, cluster II and V, cluster II and IV and cluster II and III. The maximum intra-cluster D2 distances were recorded by cluster II, while minimum distance was noticed in clusters III and V. While studying the pedigree of the genotypes, it was interesting to note that three genotypes clustered in cluster I had same pedigree. Similarly, another three grouped into cluster II also have same pedigree. On the other hand, two genotypes, though bred from same cross were grouped into different clusters. Four characters viz. days to 50 per cent flowering, specific leaf area, plant height and seed yield contributed maximum in manifestation of genetic diversity. Promising genotypes with high per se performance and genetic divergence viz., N BeG 49, ICCIL 01031, N BeG 510 and N BeG 119 from cluster I; N BeG 47 from cluster II; ICCV 09106 from cluster III and ICCV 97007 from cluster V were identified which can be utilized in crossing programme to recover an array of transgressive segregants for various traits.